Dysphoric milk ejection reflex as a new diagnostic and therapeutic challenge in lactation care - literature review - Skowrońska, Katarzyna; Chmura, Anna; Baciur, Patrycja; Środoń, Agnieszka (Journal of Education, Health and Sport, 2022)
Introduction and purpose of the work: Breastfeeding has many health benefits. The guidelines recommend breastfeeding up to 6 months of age. Many mothers stop breastfeeding early, one reason being the dysphoric ejection reflex (D-MER). It is a negative emotional reaction related to the ejection of milk. State of knowledge : D-MER has been known to science for a short time. Breastfeeding depends on many psychological factors and is regulated by many hormones, including prolactin, oxytocin, and dopamine. A sudden drop in dopamine levels is believed to be the cause of this phenomenon. The main symptoms include dysphoria, sadness, irritability, anxiety and depression. There are no registered preparations for the treatment of D-MER, psychotherapy and lifestyle changes are helpful. Summary: It is important to disseminate knowledge about D-MER to help mothers understand their breastfeeding processes. More research should be done into the safe treatment of this condition.